PENGARUH PROGRAM PELATIHAN TERHADAP KOMITMEN AFEKTIF DENGAN KETERIKATAN KARYAWAN SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT Garment XYZ Indonesia Factory 3) - Insyira Risma Medya; Intan Ratnawati (Diponegoro Journal of Management, 2023)
Employees with high affective commitment perceive themselves as aligned with company values and are willing to actively participate and contribute to company goals. Human resources in need of consistent quality in winning the competition to face the global market competition. This research aims to analyze the effect of training programs on affective commitment with employee engagement as an intervening variable at PT Garment XYZ Indonesia 3rd Factory. This study uses primary data through quantitative methods, namely data collection by distributing questionnaires involving 84 permanent employees of PT Garment XYZ Indonesia 3rd Factory as respondents and secondary data through books, journals and other sources obtained from the companies concerned. This research was a questionnaire using a saturation sampling method. The results of this study indicate that training programs have a positive effect on affective warning, training programs have a positive effect on employee engagement, employee engagement has a positive effect on affective warning, and employee engagement has a positive effect on mediating training programs and affective.